Paleozoic Exotic Blocks of Gravitational Origin in the Crimean Mountains - Vsevolod V. Yutsis; Alexander N. Stafeev; Tatiana V. Sukhanova; Abraham Del Razo Gonzalez (Geography, Earth Science and Environment: Research Highlights Vol. 5, 2025)
Based on numerous geological data obtained by the authors for several decades, the stratification of Permian and Carboniferous ancient and exotic blocks of the Crimean Mountains is performed. The sequence of geological events that caused their origin is revealed. Carnian-Norian, Rhaetian-Hettangian and early-Pliensbachian phases of collapse, sliding and burial of Paleozoic blocks are specified. The final stage (block re-deposition) is confined to the Toarcian and Aalenian ages. The data obtained allow for re-interpreting the origins of ancient exotic blocks of the Crimea. The sequence of geological events that led to the detachment, gravitational sliding, burial, and redeposition of the Carboniferous and Permian exotic blocks embedded in the Rhaetian-Liassic strata is traced to the territory of the Mountain Crimea. There are no modern outcrops of Paleozoic bedrock deposits in Crimea. The Rhaetian-Hettangian (and possibly Early Pliensbachian) stage of landsliding of blocks from ledges of bedrock massifs of Paleozoic limestones, Early Pliensbachian stage of redeposition of Paleozoic blocks from Rhaetian-Hettangian olystostromes, and Toarcian-Aalenian stage of redeposition of Paleozoic blocks from older olystostromes are clearly distinguished. At the boundary of the Norian and Rhaetian, under conditions of sub-meridional compression and folding, along the northern side of the Carnian-Norian Taurian flysch basin, the Lozovsky relatively shallow trough up to 15 km wide was isolated, separated from the basin by a chain of mountain-anticlinal rises, which served as the main source of Paleozoic limestone blocks. The blocks were detached in underwater and overwater conditions from the frontal parts of up to 1-2 km amplitude Paleozoic roof thrusts, from the bedrock massifs of Paleozoic limestones denuded by avalanche landslide denudation. In the Early Pliensbachian, during the sub-meridional stretching of the Crimean-Caucasian passive margin of the Tethys Ocean, the deepening of the Liassic rift basin took place. The most active was the Lozovsky fault with the geometry of scissors (strike-slip fault), limiting the Lozovsky zone from the south. At the same time, both the Lozovsky zone and the northern slope of the basin were fragmented by left shears of southwestern branching (horse-tail pattern), along which rhomboidal shear basins up to 3 km long and 1 km wide were formed. Paleozoic blocks re-deposited from the Rhaetian-Hettangian Olistostromes, and possibly new detachments from renewed bedrock ledges slid into these small basins.